1968
DOI: 10.1084/jem.128.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Role of Macrophages in Immunological Maturation

Abstract: Recent evidence has suggested that the initiation of antibody synthesis is a two-step process. The first step involves antigen phagocytosis and processing by macrophages (1, 2) and the second step appears to consist of the transfer of immunogenic information from the macrophage to the immunocompetent cell with subsequent initiation of antibody synthesis (3).In most instances immunological immaturity in young or immunological deficiency in adult animals is attributed to the absence of immunocompetent cells. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…eluate) cells (we have observed that approximately 10-20% of the irradiated rabbits die if they are not protected with bone marrow) and (b) to provide the recipient with macrophages and/or other cell types which, although not the predominant cell(s) required for the induction of the primary immune response, may nevertheless be necessary in small numbers in order to potentiate the immune response, or to function in a synergistic fashion. Macrophages have been shown to play an active role in promulgating the sequential steps leading to humoral antibody formation, especially in the primary response (11)(12)(13)(14)(15). It has also been demonstrated that macrophages are retained by the glass bead columns (16)(17)(18) and apparently are not eluted by the procedure utilized in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…eluate) cells (we have observed that approximately 10-20% of the irradiated rabbits die if they are not protected with bone marrow) and (b) to provide the recipient with macrophages and/or other cell types which, although not the predominant cell(s) required for the induction of the primary immune response, may nevertheless be necessary in small numbers in order to potentiate the immune response, or to function in a synergistic fashion. Macrophages have been shown to play an active role in promulgating the sequential steps leading to humoral antibody formation, especially in the primary response (11)(12)(13)(14)(15). It has also been demonstrated that macrophages are retained by the glass bead columns (16)(17)(18) and apparently are not eluted by the procedure utilized in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, l:l ratios of total PFC to plaques in the culture dish do occur when nonadherent cells are cultured, thus indicating that PPFC have maturated, but due to a lack of some property contained in the adherent cell population have failed to produce hemolysin-producing progeny. The enhancement of immunocompetence of neonatal mice to SRBC antigens by injecting them with large numbers of adult macrophages has also been reported (20). Macrophages, therefore, are probably a component of the precursor unit.…”
Section: Discussionmentioning
confidence: 87%
“…The Table shows that the growth of tumours in weanling rats from the immunized or the non-immunized (control) This experiment failed to demonstrate in a syngeneic tumour system the effects described by Beer et al (1975) of adoptive transfer of systemic immunity to allografts in sucklings by lymphocytes in the milk. This negative finding could be due either to the failure of such allergized lymphocytes to gain access to the milk or to the inability of the ingested lymphocytes to be absorbed intact.…”
Section: Resultsmentioning
confidence: 99%
“…BILLINGHAM and his colleagues (Beer et al, 1975;Parmely et al, 1976;Head et al, 1977;Parmely et al, 1977) found that in all species studied, including man and rat, viable lymphocytes and macrophages are normal components of colostrum and milk, and are present in concentrations similar to those found in peripheral blood. The lymphocytes were shown to be capable of acting as responder or stimulator cells in mixed lymphocyte cultures.…”
mentioning
confidence: 99%
See 1 more Smart Citation